Audience reception of acculturation in parenting style on Indonesian-Korean YouTube channel - Briandana, Rizki; Dwityas, Nindyta Aisyah; Mayde, Putri Calista (International Journal of Communication and Society, 2023)
The aim of this study is to investigate the audience reception of acculturation in parenting style on the Indonesian-Korean YouTube channel "Kimbab Family". Parenting is an activity aimed at helping children to meet challenges from the environment as well as developing. This study focuses on the interpretations of young adult audiences on the YouTube channel. Thirty-six informants were selected as primary data using FGD techniques. From the results obtained by the researchers through FGDs with the informants, it was shown that the audiences reception on the YouTube channel is diverse and influential. By combining Indonesian and Korean parenting styles, the Kimbab Family has become a source of inspiration and a role model for effective parenting. This research highlights the need for further exploration of the role of media platforms in shaping audience perceptions and expectations, as well as the potential benefits and challenges of incorporating diverse cultural influences in parenting practices.